1998
DOI: 10.1038/sj.bmt.1701396
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of acute graft-versus-host disease and recurrent leukaemia in patients undergoing allogeneic haemopoietic stem cell transplantation from sibling donors with methotrexate and dose-monitored cyclosporin A prophylaxis

Abstract: Summary:One of the major aims of allogeneic haemopoietic stem cell transplantation has been the effective suppression of graft-versus-host disease (GVHD) without loss of a graft-versus-leukaemia effect. For GVHD suppression, one of the most frequently used regimens has been the combination of cyclosporin (CsA) and a short course of methotrexate (MTX) although the optimal usage of these agents remains unclear. Here, we report the results of 55 patients with standard risk leukaemia who have undergone allogeneic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…In all, insufficient post transplant immunosuppression is one of the most important determinants of relapse risk through its impact on the potency of an immunologically mediated graft vs. malignancy effect. This is particularly relevant in patients undergoing allogeneic HSCT using a reduced-intensity conditioning regimen, where a graft vs. malignancy effect represents the dominant anti-tumour mechanism [4,[17][18][19][20][21][22]. Therefore, a model that predicts ciclosporin pharmacokinetics and dose requirements to achieve the desired therapeutic target in an individual HSCT patient would be highly useful.…”
Section: Introductionmentioning
confidence: 99%
“…In all, insufficient post transplant immunosuppression is one of the most important determinants of relapse risk through its impact on the potency of an immunologically mediated graft vs. malignancy effect. This is particularly relevant in patients undergoing allogeneic HSCT using a reduced-intensity conditioning regimen, where a graft vs. malignancy effect represents the dominant anti-tumour mechanism [4,[17][18][19][20][21][22]. Therefore, a model that predicts ciclosporin pharmacokinetics and dose requirements to achieve the desired therapeutic target in an individual HSCT patient would be highly useful.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, therapeutic ranges used to monitor CsA therapy remain empirical 22 and heterogeneous. 17 Only two studies, mainly performed in adults, have shown the positive impact of a monitored CsA regimen on aGVHD incidence and outcome, 23,24 but the results cannot be transposed to children. As goal-oriented individualized CsA regimens require accurate knowledge of the values of effective blood concentrations, the aim of our study was to clarify relationships between TBC and aGVHD incidence, in a population including only children receiving allogeneic MSD-or UD-SCT.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Improvement in prophylactic GVHD regimens or treatments remains one of the greatest challenges. 8,9 The most frequently used prophylaxis for GVHD includes the combination of cyclosporine (CsA), corticosteroids, short-course methotrexate, and/or antithymocyte globulin.…”
mentioning
confidence: 99%